Would the Cephalic Development in the Purebred Arabian Horse and Its Crosses Indicate a Paedomorphic Process? (2022)
This study examined paedomorphosis in PAH and F1 crossbreds. A sample of 99 horses was selected from 40 different breeders and consisted of three groups: stallions (n = 16), mares (n = 53), and geldings (n = 30), ranging from 10 months to 27 years in age. All horses presented a concave celloid lateral left head profile in the acquired photographic images. The hypothesis proposed in this study suggested the lateral profile of the head in juveniles was representational in the adult form due to the neonate’s facial bones (part of the splanchnocranium) developing at a different rate to those of the skull. The methodology utilized geometric morphometrics to identify 23 landmarks so as to identify profile curvature indicative between the three groups (stallions, mares, and geldings). Principal component analysis reduced the number of variables to 14 examinable landmarks. Using a two-NPMANOVA and multivariate regression test, it was demonstrated that an isometric relationship between the concave celloid profile in the juvenile and its adult counterpart existed. This result supported the hypothesis that PAH and F1 crossbreds expressed a paedomorphic trait due to the adult form retaining the concave celloid profile identified in the juvenile.